Verify that -(-x) = x for (i) x = 11/15 (ii) x = -13/17

By Mandeep Kumar|Updated : May 23rd, 2023

To verify: -(-x) = x

(i) x = 11/15

Now, put the given value of x in -(-x) = x.

 -(-x) = x

-(-11/15) = 11/15

We know that two negative signs, one of which turns over, add up to form a positive. So, the two negative signs on the left side (LHS) will be changed into a positive sign.

11/15 = 11/15

Here, LHS = RHS, hence it is verified that -(-x) = x.

(ii) x = -13/17

-(-x) = x

-[-(-13/17)] = -13/17

-[13/17] = -13/17

-13/17 = -13/17

Again, LHS = RHS for -(-x) = x where x = -13/17, hence -(-x) = x verified.

Verification of -(-x) = x for x = 11/15 and x = -13/17

A rational number is one that can be expressed in the form p/q, where p and q are integers and q = 0. Every integer and fraction is a rational number. When we multiply or divide the numerator and denominator of a rational number by a non-zero integer, we get a rational number that is said to be equivalent to the given rational number.

  • Positive rational numbers, zero rational numbers, and negative rational numbers are the three types of rational numbers. 
  • It is a positive rational number if the numerator and denominator are both positive integers or both negative integers.
  • It is a negative rational number if either the numerator or the denominator is a negative integer.
  • As a rational number, 0 can neither be positive nor negative.


Verify that -(-x) = x for (i) x = 11/15 (ii) x = -13/17

To verify -(-x) = x put the given values of x in the given equation. After that, solve the equation to make the left hand side equal to the right hand side. One concept that is used while solving the equation is that when two negative signs come together it is changed into a positive sign.


write a comment

Follow us for latest updates